What shall our pleasures be - Ellis, Lucy (My University, 1895)
Introduction: Pleasure does not consist in doing just what one likes or pleases, that is a mere determination of the will. But it is rather a kind of feeling which stimulates the will to action tending to sustain or produce it, to sustain is actually present and produce it if represented in idea. It is that which is pleasing to the intellect or the senses. It cannot be obtained by simply making it the only end and aim for performing some act, as the pleasurers of merely animal life are obtained only on condition of not being sought directly and so it is with the pleasurers of thought and study they can be enjoyed only in the highest degree by those who have an ardor of curiosity so as to carry the mind temporarily away from self and it’s sensations. In art we must forget the creative faculty if we want the intense and exquisite pleasure of imagination.
Citation: Ellis, Lucy. What shall our pleasures be. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Pleasure; Art; Imagination; Theses; Manuscripts (documents)